The Case of Catherine Dammartin: Friends, Fellows, and the Survival of Celibacy in England’s Protestant Universities - Kesselring, K. J. (Renaissance and Reformation / Renaissance et Réforme, 2021)
Catherine Dammartin began her adult life as a nun in Metz but ended it in 1553 as a wife in an Oxford college. First laid to rest in Christ Church Cathedral, her corpse was later removed as a pollutant then finally restored in a ceremony that saw her bones mixed with those of the virgin St. Frideswide. This article revisits Dammartin’s story to explore what it can tell us of the affective, sexual, and gendered dimensions of England’s Reformation. It argues that the Oxford Protestants who arranged her reburial did so to intervene in the debate about clerical marriage, a debate in which they were only partially successful. Dammartin was one of the first and last wives to live in college for a very long time. Her story offers a reminder that despite the shift to clerical marriage, England’s universities remained—somewhat distinctively within Protestant Europe—sites where celibacy continued as the norm: sites of homosocial bonding and fellowship that served as a counterpoint to otherwise dominant codes of masculine behaviour that privileged the Protestant paterfamilias.